Cu–citric acid metal–organic framework: Synthesis, characterization and catalytic application in Suzuki–Miyaura cross‐coupling reaction and oxidation of sulfides. (13th October 2021) - Koolivand, Mostafa; Nikoorazm, Mohsen; Ghorbani‐Choghamarani, Arash; Tahmasbi, Bahman
Abstract : Citric acid with three carboxylic groups was used as an outstanding chelating agent was utilized for the preparation of Cu–citric acid metal–organic framework (Cu–CA–MOF). The prepared MOF was characterized by FT‐IR, XRD, EDS, AAS, SEM, WDX and BET analysis. N2 adsorption–desorption isotherms indicated acceptable BET surface area for Cu–CA–MOF. SEM images were shown that Cu–CA–MOF has geometric polyhedral shapes. Also, catalytic activity of Cu–CA–MOF successfully examined for the Suzuki–Miyaura cross‐coupling reaction and chemoselective oxidation of sulfides to sulfoxides. Abstract : A novel and well‐characterized Cu–CA–MOF with a citric acid ligand was prepared. The Cu–CA–MOF has been applied as efficient catalyst in the Suzuki cross‐coupling and oxidation of sulfides under mild conditions.